ANALISIS FAKTOR RISIKO DIABETES MELLITUS TIPE 2 - Karlina, Nonok; Wulandari, Angernani Trias; Amalia, Lisa Rizky (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: The International Diabetes Federation (IDF) states that in 2019, 63 million people aged 20-79 years had diabetes worldwide, representing a prevalence of 9.3% of the total population of that age group. In the elderly group (65-79 years) it is estimated that the prevalence of diabetes will further increase to 19.9%. The majority of the incidence of diabetes mellitus (DM) occurs in the elderly. Because the elderly body has experienced changes in tolerance to glucose. The aim of the study was to determine the factors associated with the incidence of diabetes mellitus in the elderly at the Binangun Health Center, Cilacap Regency in 2023. The type of research used is quantitative research using explanatory research, to find an explanation for the occurrence of a phenomenon. The result of this research is a description of the causal relationship. The sample used was the entire population at the research site, namely 55 respondents. The results showed that there was a relationship between physical activity (p value: 0.010) and stress levels (p value: 0.000) on the incidence of diabetes mellitus. It is recommended that patients have the awareness to always do regular physical activity, make lifestyle changes towards a better direction so that they will get a good quality of life for the prevention of complications and poor patient conditions.Keywords: Physical Activity, Diabetes, Stress